Shaping national rare diseases definition in Saudi Arabia: outcome from health ecosystem multisectoral workshop - Abozaid, Ghada Mohammed; Al-Omar, Hussain Abdulrahman; Alrabiah, Abdulaziz; Alomary, Hiba; McKnight, Amy Jayne (Frontiers in Pharmacology, 2025)
IntroductionRare diseases are characterized by low prevalence, a profound impact on patients, and significant challenges in accessing treatment. In Saudi Arabia, the absence of an official definition hampers policymaking, resource allocation, and orphan drugs accessibility. This study aimed to address this gap by proposing a definition of rare diseases using inputs and views from a Saudi multi-stakeholder workshop.MethodsA 1-day workshop was hosted in collaboration with the Saudi Health Council in Riyadh on 5 June 2023, involving 59 participants from various sectors, including clinicians, policymakers, patient advocates, and industry professionals. Using the Vevox® platform, participants engaged in structured activities comprising a demographic survey and 10 interactive voting sessions. Preferred qualitative and quantitative criteria for defining rare diseases were identified and analyzed using descriptive statistics and thematic and content analysis of open-ended questions.ResultsThe findings indicated a strong preference (96%) for an integrated definition combining qualitative and quantitative criteria. Key qualitative terms such as “Disease” (62%), “Serious” (53%), and “Disorder” (51%) were favored for their clarity and broad applicability. “Genetic” etiology was preferred by 91% of participants, citing its relevance and data availability. Patient-centered criteria, including “life-threatening” (73%) and “considerable reduction in quality of life” (91%), were emphasized. Economic and resource-focused considerations, such as “Lack of Resources” and “Combined Efforts to Prevent” (each at 60%), reflected key unmet needs in the current healthcare landscape. Among quantitative criteria, “Prevalence” (82%) emerged as the most accepted, aligned with international practices, although opinions were mixed on the inclusion of population size thresholds, underscoring the definitional complexity of defining RDs with both precision and flexibility.DiscussionThis study provides a foundational basis and scientific root for defining rare diseases in the Saudi context, addressing key gaps in healthcare policies. By integrating evidence-based, patient-centered, and resource-oriented criteria, the proposed definition supports equitable access, improved patient care, and sustainable innovation, in alignment with Saudi Arabia’s Vision 2030 goals. Further refinement with broader stakeholder inputs is essential for the successful integration of Saudi healthcare policies.